Seasonal Changes in Upper Thermal Tolerances of Freshwater Thai Fishes - Tongnunui S. (2023)
Seasonal change inferred to climate change inevitably influences Critical thermal maximum (CTmax) of riverine fishes. In this study, we investigated CTmax as thermal tolerance for four common riverine fishes, i.e., Danio regina, Channa gachua, Rasbora caudimaculata and Mystacoleucus chilopterus, in the Kwae Noi river system in western Thailand. The acute thermal tolerance was lower in the wet season (mean river temperature ∼25 °C) and higher in the dry season (mean river temperature ∼23 °C) with medians of wet season-CTmax for those four fishes of 35.3 ± 0.4, 36.2 ± 0.5, 37.3 ± 0.5 and 37.5 ± 0.6 °C, respectively, and high values of dry season-CTmax of 37.4 ± 0.5, 38.3 ± 0.5, 38.7 ± 0.7 and 39.1 ± 0.5 °C, respectively. The variations of CTmax for all of the four species in this study, throughout the wet and dry seasons, attribute to their seasonal plasticity in response to the dynamics of thermal stress. Under climate variability and climate change with increasing the higher temperatures of air and river, and altering the habitat, R. caudimaculata and M. chilopterus had higher capacities to tolerate the acute heat stress across wet and dry seasons.